Prevalence, molecular identification and genotyping of the crayfish plague pathogen, Aphanomyces astaci in major narrow-clawed crayfish (Pontastacus leptodactylus Eschscholtz, 1823) populations from Türkiye - Akhan, Süleyman; Çağatay, İfakat Tülay; Berber, Selçuk; Taştan, Büşra; Taştan, Yiğit; Dalar, Tuba (Walter de Gruyter GmbH, 2024)
Abstract Introduction Crayfish plague is considered the most important crayfish disease globally. It is caused by the fungus-like agent, Aphanomyces astaci. This study aimed to identify and determine the prevalence of A. astaci using PCR in narrow-clawed crayfish (Pontastacus leptodactylus) populations from across Türkiye. Material and Methods A PCR was carried out with primers specific to the internal transcribed spacer region of the A. astaci pathogen on both telson and abdominal cuticle tissues from crayfish individuals from 41 different locations. Results Aphanomyces astaci was detected in the crayfish from 34 of the locations. Molecular diagnosis showed the prevalence rates of A. astaci to be between 0% and 68.2%. For 7 of the 34 locations, the strain of A. astaci was determined. Microsatellite analysis of tissue from individuals with positive PCR results revealed the A. astaci genotypes in seven populations. Genotype B was found to be the predominant genotype responsible for crayfish plague in Turkish crayfish populations. The Psl genotype (genotype B) was determined in six of the populations, and the As genotype (genotype A) was detected in only one. Conclusion Crayfish plague poses a significant threat to crayfish populations, necessitating the development of rapid, highly sensitive diagnostic methods. An understanding of the sensitivity of the PCR detection method and of the prevalence and genotyping of A. astaci in Turkish crayfish populations has been gained from this study.
Keywords: crayfish; pcr; clinical samples; aphanomyces astaci; Veterinary medicine; SF600-1100; Article